Teaching Resources: World War II: Focus on Asia (Education About Asia, 2021)
This month marks the end of World War II. The following archives on this topic constitute only a sample of EAA published articles, but represent multiple perspectives and individuals who in these turbulent years had substantial impact on other people's lives.
Keywords: China; East Asia; Education; Japan; Korea; Northeast Asia; United States; World History